Study of Furrow Planting System in the Limestone Reclamation Area of PT. "X", East Java Province - Fairus Atika Redanto Putri; Achmad Ar-Rasyid; Esthi Kusdarini (Nusantara Civil Engineering Journal, 2026)
The mining industry contributes significantly to economic development, but it also causes environmental impacts in the form of land degradation, particularly in limestone mining areas, which typically have very thin topsoil layers. This condition complicates the revegetation process and slows down the ecological recovery of the land. This study examines the strip planting system in the limestone mine reclamation area owned by PT X, East Java Province. The objectives of this study are to describe the technical stages of implementing the furrow planting system, describe the actual conditions of the furrow planting system implementation, compare the furrow planting system with the conventional system, and implement the furrow planting system on new land. The methods used are a combination of qualitative and quantitative approaches. Primary data required included soil quality, surrounding vegetation, planting distance, and row spacing, while secondary data required included WIUP data, RR documents, geological maps, plant height, plant diameter, and number of leaves. The results of the study show that the furrow planting system produces optimal teak growth compared to the conventional system. In addition to providing better vegetation growth, the furrow planting system has also been proven to be more efficient in the use of topsoil, requiring only 640 m3/Ha compared to 3000 m3 in the conventional system. Implementing this system on a new 3.2-hectare site is projected to require 2,306 trees and 2,234 m³ of topsoil, with seedlings sourced from stem cuttings. These results indicate that the ridge planting system is an effective and efficient method for supporting sustainable mine land reclamation.